The Impact of Corporate Social Responsibility on Brand Equity via Structural Modeling: A Case Study of Mobile Phone Users in Laghouat - BAADJ , Hachemi; BOUAKKAZ , Hadjer (Social Empowerment Journal)
This study aimed to determine the impact of corporate social responsibility on the brand equity of mobile phone users. Structural equations served as a primary methodology and experimental approach, employing various advanced methods and techniques within the humanities domain. The study delineated its parameters through an independent variable encompassing corporate social responsibility to stockholders, the environment, customers, and the local community, while brand equity served as the dependent variable. To fulfill these objectives, a questionnaire was formulated and distributed to a sample comprising 354 subjects. The gathered data underwent analysis using SMARTPLS software. The findings revealed a significant effect of corporate social responsibility, accounting for approximately 32.2%, on the brand equity of the Ooredoo company. Consequently, the study recommends that companies invest in CSR activities to foster a sustainable brand and attain enhanced brand equity.